2011
DOI: 10.1162/artl_a_00045
|View full text |Cite
|
Sign up to set email alerts
|

Information Content of Colored Motifs in Complex Networks

Abstract: We study complex networks in which the nodes of the network are tagged with different colors depending on the functionality of the nodes (colored graphs), using information theory applied to the distribution of motifs in such networks. We find that colored motifs can be viewed as the building blocks of the networks (much more so than the uncolored structural motifs can be) and that the relative frequency with which these motifs appear in the network can be used to define the information content of the network.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 66 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…An interesting perspective regarding such graphs is to investigate the complexity [3,4] or information content of a graph [5]. While Shannon information theory [5][6][7] and counting symmetries [8,9] have been applied to measure information content/complexity of graphs, little has been done, by contrast, to demonstrate the utility of Kolmogorov complexity as a numerical tool for graph and real-world network investigations. Some theoretical connections between graphs and algorithmic randomness have been explored (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting perspective regarding such graphs is to investigate the complexity [3,4] or information content of a graph [5]. While Shannon information theory [5][6][7] and counting symmetries [8,9] have been applied to measure information content/complexity of graphs, little has been done, by contrast, to demonstrate the utility of Kolmogorov complexity as a numerical tool for graph and real-world network investigations. Some theoretical connections between graphs and algorithmic randomness have been explored (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, we adopt the notion that N-node subgraphs are the basic building blocks, but do not necessarily occur frequently in a network. Adami et al (2011) studied undirected colored graphs (where nodes are labeled with different colors) and showed that the relative frequency of the colored motifs can be used to define the information content of the network. Here, we consider subgraphs that are directed graphs which could contain cycles.…”
Section: Network Subgraphs (N-node Subgraphs) Vs Network Motifsmentioning
confidence: 99%
“…There has been some work on motif detection using colors only in nodes [9], but not with colored edges, even if it was acknowledged that incorporating connection types would lead to richer results [6]. The work by Adami et al [5] considered the case of colors only in nodes and uses an entropy-based measurement to determine significance. Quian et al [10] also use colors solely in nodes and swap colors in the network, that is, the randomized networks are topological equivalent to the original, but with a different permutation of the colors in the nodes.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in metabolic networks, we can distinguish between two sets of nodes: reactions and chemical compounds [4]. By ignoring these labels we may be missing important patterns, and it has been shown that by associating different colors to the Pedro Ribeiro • Fernando Silva CRACS & INESC-TEC, DCC-FCUP, Universidade do Porto, Portugal e-mail: pribeiro@dcc.fc.up.pt, fds@dcc.fc.up.pt nodes, their information content is richer [5]. The same can be said about edges, and previous experiments have shown that we would gain if it was possible to distinguish between different types of connections in biological networks [6].…”
Section: Introductionmentioning
confidence: 99%